Electrical Diseases of the Heart Volume 1: Basic Foundations and Primary Electrical Diseases - Gussak, Ihor; Antzelevitch, Charles (Springer London : Imprint: Springer, 2013)
The past two decades have witnessed an explosion of knowledge and radical changes in our understanding of the molecular, ionic, genetic, and pharmacologic basis of electrical diseases of the heart. Electrical diseases of the heart are heritable arrhythmogenic clinical entities that may share common clinical and genetic features, yet may be distinctly different in their genesis, prognosis, and management. Notably, both congenital and acquired electrical diseases of the heart are receiving increased recognition as a result of important advances in genetic analysis.   In this second edition of Electrical Diseases of the Heart, the Editors' goal has been to embrace and highlight the explosion of knowledge that our field has witnessed since the publication of the first edition.  The approach continues to be one of bridging basic and clinical science in an attempt to advance meaningfully our understanding of heart disease and identify the knowledge gaps that exist. This volume covers the basic foundations and primary electrical diseases and with the companion volume provides the latest developments in the field of experimental and clinical cardiac electrophysiology, genetics, pharmacology and interventional therapies of various clinical arrhythmogenic entities.   Residents, fellows and physicians in cardiology and electrophysiology will gain valuable insight into the latest developments in the field of cardiac electrophysiology and clinical electrocardiology by reading this book, including expert review of the genetic and epidemiologic considerations, diagnostic and therapeutic modalities of the newly discovered clinical syndromes and electrocardiographic phenomena, and their correlation with the most recent advances in the basic science.